Frações da matéria orgânica e atributos físicos de um vertissolo em sistemas de consórcio de longa duração - Ferreira Filho, Roberto Monteiro (2017)
The effects of medium- and long-term smallholder farming systems in the Brazilian tropical seasonal dry forest that promote changes in the organic matter fractions (MOS) and in the physical attributes of Vertisols are unknown. Our aim here, was to evaluate the impact of different land uses on labile carbon, recalcitrant fractions of MOS and physical properties of Vertissolo under common bean – maize – fava bean rotation. This study was carried out at Queimadas, Paraíba, Brazilian Northeast in a Vertissol under field conditions. Soils samples were collected from four environments: MN: Caatinga – This environment contains only native plant species from Caatinga biome (Control); CS: Secondary growth vegetation – This environment contains typical regional tree species (native and exotic plant species) over 10 years old; and SC8 and SC44: These environments were characterized by medium (8 years) and long-term (44 years) smallholder farming systems in a common bean – maize- fava bean rotation. We establish for each environemt one plot of 800 m2. We collected soil samples from four sub-plots in each plot using a randomized systematic sampling. In each sub-plot we five and three soil samples to evaluate the fractions of the MOS and the physical attributes, respectively. For each sub-plot we also collected soil samples in three depths: 0.00 - 0.05 m; 0.05 - 0.10 m; and 0.10 - 0.20 m. Light-fraction of soil organic matter content (MOL), carbon of MOL (C-MOL), nitrogen of MOL (N-MOL), soil total organic carbon (TOC), labile carbon (LC), total nitrogen (TN), soil carbon stock (SCS), soil nitrogen stock (SNS), carbon fraction of humic substancec [i.e., humin (CFHU), humic acids (CFAH) and fulvic acids (CFAF)], bulk density (Bd), total porosity (Pt), soil macroporosity (Ma), soil microporosity (Mi), field capacity (CC), permanent wilting point (PMP), soil available water (AD) and soil resistance to penetration (RP) were investigated. We found the highest values of MOL (2.38 g kg-1), C-MOL (0.77 g kg-1), N-MOL (0.07 g kg-1), C-FHU (5.24 g kg-1), C-FAH xviii (1.9 g kg-1) and C-FAF (1.74 g kg-1) in the MN environment. The highest SCS values were observed in the both MN (10.89 Mg ha-1) and CS (10.58 Mg ha-1) environments in the 0.00 – 0.05 m depth, while the highest values of SNS were observed in the CS (1.60 Mg ha-1) and MN (1.55 Mg ha-1) environments in the 0.10 – 0.20 m depth. When we compared the MN environment with the SC8 and SC44 environments, we have found that these last two environments presented lower values of MOL, C-MOL, N-MOL, COT, NT, ECS, ENS, C-FHU, C-FAH and C-FAF in the order of 25.6 and 48.7 %; 52 and 85.7 %; 57.14 and 85.7 %; 13 and 44 %; 18.5 and 38.5 %; 11.26 and 43.7 %; 11.1 and 42.6 %; 8.55 and 42 %, respectively. The highest values of Ds were found in the MN (1,5 g cm-3) environment and in the 0.10 - 0.20 m depth (1,35 g cm-3). The highest values of Ma were observed in the SC8 and SC44 environments and in the depth of 0 - 0.05 m (0.07; 0.06 and 0.05 m3m-3), respectively. The highest RP (2.25 kg cm-2) was observed in the SC44 environment within the 0.10 - 0.20 m depth. No significant differences were found between the land uses and sampling soil depths for the CL, Pt, Mi, CC, PMP and AD. The medium- and long-term common bean – maize – fava bean rotation alter the labile and recalcitrant fractions of MOS, as well as the physical properties of a Vertisol in field conditions. The soil depth (0.00 - 0.05 m) presented the highest content of MOL, COT, NT, SCS, CFHU, CFAH and CFAF in relation to the subsurface depths (0.05 – 0.10 m and 0.10 – 0.20 m). We found no differences between the soil physical properties (Ds, Ma and RP) in both SC8 and SC44 environments, but they differed from the MN environment. There were no differences in soil water retention relationship among all the studied environments. Our study lighlight the importance to consider the trends of soil carbon contents of humic acid fractions and fulvic acids as potential indicators of changes caused by different land use into soil profile.